2007
DOI: 10.1371/journal.pbio.0050300
|View full text |Cite|
|
Sign up to set email alerts
|

Distinct Mammalian Precursors Are Committed to Generate Neurons with Defined Dendritic Projection Patterns

Abstract: The mechanisms that regulate how dendrites target different neurons to establish connections with specific cell types remain largely unknown. In particular, the formation of cell-type–specific connectivity during postnatal neurogenesis could be either determined by the local environment of the mature neuronal circuit or by cell-autonomous properties of the immature neurons, already determined by their precursors. Using retroviral fate mapping, we studied the lamina-specific dendritic targeting of one neuronal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
101
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(105 citation statements)
references
References 53 publications
3
101
1
Order By: Relevance
“…5e,f), as previously reported 36,37 . To compare the arborizations, we determined the depth of the initial branch point, a surrogate measure of dendritic innervation patterns 37 , and found that the dendrites extending to the superficial EPL by the Gmip KD superficial GCs were similar to those of the control group ( Fig. 5e,f; for other dendrite measures, see Supplementary Fig.…”
Section: Identification Of Gmip As a Girdin-interacting Proteinsupporting
confidence: 84%
See 2 more Smart Citations
“…5e,f), as previously reported 36,37 . To compare the arborizations, we determined the depth of the initial branch point, a surrogate measure of dendritic innervation patterns 37 , and found that the dendrites extending to the superficial EPL by the Gmip KD superficial GCs were similar to those of the control group ( Fig. 5e,f; for other dendrite measures, see Supplementary Fig.…”
Section: Identification Of Gmip As a Girdin-interacting Proteinsupporting
confidence: 84%
“…In the GCL, GCs not only exhibit distinct morphologies and dendritic projection patterns from sub-layer to sub-layer, but also have different synaptic innervations and inhibitory functions for olfactory inputs 36,37 . We found that Gmip KD increased the percentage of new GCs distributed to the superficial layers of the GCL owing to the insufficient deceleration of migrating neurons in the OB, although the redistributed cells' dendritic morphology was similar to that of the naive superficial GCs (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, since impaired PCP signaling decreases NPC migration into the outer GCL (Fig. 2), it is possible that the altered morphology of the GCs, such as the longer primary dendrite, is partly due to their altered migration and localization [60]. Roles for Wnt signaling in neurite formation have been reported in invertebrates and vertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…In the cerebral cortex, different interneuron categories originate from defined subsets of subpallial progenitors, whose developmental potentialities depend on their location [62][63][64] and on the time of their generation [45, 65,66]. Finally, the production of olfactory bulb interneurons is sustained by separate progenitor pools, restricted in space [67][68][69][70] and time [71][72][73]. Thus, while the most common strategy to generate the variety of CNS interneurons relies on dedicated precursors that differentiate according to cell-intrinsic programs, those of the cerebellum are produced by naive progenitors under the influence of extrinsic instructive cues.…”
Section: Concluding Remarks: a Peculiar Neurogenic Strategymentioning
confidence: 99%